Given the system of equations:
• y = x² - 4
,
• y = -2x - 5
Let's find the solution(s) to the system.
To find the solution, eliminate the equivalent sides and equate the expressions.
We have:
![x^2-4=-2x-5](https://img.qammunity.org/2023/formulas/mathematics/high-school/8f630gjaajkbjadvcun28sy8zgrztqe6qu.png)
Move all terms to the left and equate to zero.
Add 2x and 5 to both sides:
![\begin{gathered} x^2+2x-4+5=-2x+2x-5+5 \\ \\ x^2+2x+1=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/oa0vttmo3kun21ekv5wdex4i2o3fg7g8tc.png)
Factor the left side of the equation using the perfect square rule:
![\begin{gathered} x^2+2x+1^2=0 \\ \\ x^2+2\cdot x\cdot1+1^2=0 \\ \\ (x+1)^2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/5a1bo9ptccvaq2x29cyliie2bycj4re6xw.png)
Solving further:
![x+1=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/avzmne2ewi9dxdh1bg3xd0t60w6hnmnean.png)
Subtract 1 from both sides:
![\begin{gathered} x+1-1=0-1 \\ \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1f1j4lqdhfbvrl93soyxs9s1i9nowmuumz.png)
Now, substitute -1 for x in either of the equations and solve for y.
Let's take the first equation:
![\begin{gathered} y=x^2-4 \\ \\ y=-1^2-4 \\ \\ y=1-4 \\ \\ y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/y0gg2ab0uh4iys1fzd1rvke9i6ncr4crpj.png)
Therefore, we have the solutions:
x = -1, y = -3
In point form:
(x, y) ==> (-1, -3)
ANSWER:
A. (-1, -3)